Effect of Adolescent Health Policies on Health Outcomes in India - Sayooj Sahadevan; Maureen Dar Iang; Fekri Dureab (MDPI AG, 2023)
Adolescence is a crucial phase marked by significant physical, psychological, emotional, and social changes. India has the world's largest adolescent population. Understanding and addressing their health needs is vital for the nation's social, political, and economic progress. The primary aim of this study was to evaluate the main adolescent health policies and strategies implemented from 2006 to 2020 and analyze the outcomes for adolescent health in India. To achieve this objective, the research adopted a mixed-method approach, combining qualitative and quantitative analyses of health policies, strategies, and programs implemented since 2005. Additionally, data from the most recent three Demographic Health Surveys (DHSs) were analyzed and compared to assess changes in adolescent health indicators after implementing these policies/strategies. The findings focused on India's major adolescent health policies, namely the Adolescent Reproductive and Sexual Health (ARSH) Strategy2005, Rashtriya Kishor Swasthya Karyakram (RKSK) 2014, and the School Health Program 2020. All the strategies and programs aim to provide a comprehensive framework for sexual and reproductive health services, expand the scope of adolescent health programming, and address various health aspects. The analysis highlighted strengths in targeted interventions, monitoring, and promotion but weaknesses in awareness, societal barriers, and healthcare worker participation. Opportunities include female-friendly clinics and education about early pregnancy, while addressing substance abuse and training volunteers remain challenges. Family planning has improved with higher contraception usage and a decline in unmet needs. The incidence of violence decreased, and positive health behaviors increased, such as condom use. However, challenges remain, including limited access to health services, concerns about female providers, and low health insurance coverage. Nutrition indicators showed a slight increase in overweight/obesity and anemia rates. In conclusion, progress has been made, but certain adolescent health aspects still require attention. Further efforts are needed to achieve universal health coverage and improve adolescent health outcomes. Conducting targeted awareness campaigns, strengthening health worker and NGO engagement, and combating the increasing prevalence of overweight and obesity among adolescents are recommended.